Financial Determinants of Public Investment Strategic Management (European Journal of Marketing and Economics, 2019)
Strategic management of investment projects in the public sector seems to be one of the more complex phenomena observed in the sphere of implementation of public investment tasks. The complexity of investment processes is influenced by a number of factors with varying impact. First of all, attention should be paid to the high capital intensity of public investment and the associated significant extension of the investment cycle. As a result of the impact of these factors, public investments in most cases require large capital expenditures, and their implementation takes much longer than, for example, in industry. Secondly, public entities responsible for the implementation of investments are in a quite specific situation, which means the continuous development of various components of technical and social infrastructure. Therefore, it is necessary to indicate the strategic dimension of these investments and, consequently, the necessity to use appropriate methods of financing and managing these investments. In principle, the main source of financing public investment is, and probably will remain, the state budget, and in relation to local self-government - the budgets of these units, and therefore public resources. The purpose of the paper is therefore to present the complexity of the issue of financing public investments in relation to the identified conditions for the development of socio-economic infrastructure, financed from public funds. The study has undertaken theoretical research on public investment and research on the possibility of implementing effective management methods in strategic perspective.
Keywords: management in public, public finance, strategic management, investments.